CHALLENGES OF THE SCHOOL PHYSICAL EDUCATION IN THE TEACHING MEDIUM FRONT TO THE NEW SOCIETY (Fiep Bulletin - online, 2014)
The present article tries to show a study of the current reality of the school Physical education in the High School and the new emerging slopes in the area of the Physical education. It is verified today, a high sports index in the atmospheres school, proceeding mainly of the identity lack while it curriculum disciplines of the School Physical education. The technological progress, through the media and computer science, altered the adolescents' behavior significantly. In this sense, if it turns indispensable a new methodology in the field of the School Physical education aided by the new Law of Guidelines and nº9394 Bases of, December 20, 1996, front to the new methodologies, open, critical - higher, constructivist and critical-independent the ones which, with their peculiarities and similarities, they emerge as the best road to be proceeded so that the School Physical education own identity, forming a discipline obligation with the transmission and production of knowledge in all of the teaching levels, mainly in the High School.
Keywords: Physical Education; High School; Methodology of the Physical Education